2021
DOI: 10.1111/acel.13383
|View full text |Cite
|
Sign up to set email alerts
|

Chronological and biological aging of the human left ventricular myocardium: Analysis of microRNAs contribution

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
1
5
0
1
Order By: Relevance
“…Fibrosis is also a well-known arrhythmogenic substrate as it can hamper proper impulse propagation [ 4 ]. Recently, similar observations have been reported in humans and large animals (pig) in relation to age and fibrosis (amount and spatial distribution), and specifically related to collagen as chief component of the ventricular extracellular matrix [ 5 , 6 ].…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Fibrosis is also a well-known arrhythmogenic substrate as it can hamper proper impulse propagation [ 4 ]. Recently, similar observations have been reported in humans and large animals (pig) in relation to age and fibrosis (amount and spatial distribution), and specifically related to collagen as chief component of the ventricular extracellular matrix [ 5 , 6 ].…”
Section: Introductionsupporting
confidence: 56%
“…This fibrosis impairs cardiac muscle relaxation and may result in heart failure. LV collagen deposition was reported to be higher in elderly individuals than in young individuals [ 3 , 5 , 51 ]. This increase in the degree of LV fibrosis was also shown to lead to ventricular dysfunction [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is an important risk factor for ischemic heart disease and heart failure (62-64). Previous studies have identified diverse cell autonomous and nonautonomus pathways involved in regulation of cardiac and vascular aging processes (65)(66)(67)(68)(69). In vitro and in vivo studies, focusing on protective effects of PACAP against ischemic events, confirmed that PACAP confers significant anti-aging effects in the cardiovascular system (70).…”
Section: Ischemic Heart Disease and Heart Failurementioning
confidence: 88%
“…Heart aging can be triggered by a variety of complex factors, including the decline of stem cell functionality and quantity [11] , cardiomyocyte senescence [12] , DNA damage [13] , overproduction of reactive oxygen species (ROS) [14][15] , and telomere shortening [13] , as well as the activation of aging genes [6][7] . Some molecules and signaling pathways have also been found to be involved in the regulation of heart aging [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%